Accelerated lifetime testing of a levitated micro-gyroscope - Woo, Yew Shun. (2009)
Micro-electronic fabrication technologies have recently been applied to produce novel micro-mechanical devices such as motors, sensors, and actuators. Their small size and easy integration with micro-electronics invite innovative research. One device with widespread application would be an electrically suspended microgyroscope. Despite this, there have been little researches done on the lifetime of a levitated micro gyroscope. Thus a lifetime characterization of a levitated micro gyroscope will provide valuable information to aid in the improvement in micro gyroscope designs. In this project, the micro gyroscope will be subjected to elevated temperature to accelerate its lifetime. Effects on the micro coil will also be investigated. The first phase of this project will involve: 1. Testing the functionality of the equipments used. 2. Developing a system using LabVIEW (program) to aid in taking measurements. 3. Fabrication of the micro coils (stator) of the micro gyroscope. Phase II will involve the accelerated failure tests. An experimental setup automated by LabVIEW is successfully built with consideration on the noise generation by the environment. Finite element method (FEM) is also conducted to analyse and predict the failure.